Answer:
1)[tex](g+h)(x)=4x^2+x+2[/tex]
2) [tex](g-h)(x)=-4x^2+x+2[/tex]
3)[tex](g\bullet h)(-3)=-36[/tex]
Step-by-step explanation:
The given functions are
[tex]g(x)=x+2[/tex]
and
[tex]h(x)=4x^2[/tex]
1) [tex](g+h)(x)=g(x)+h(x)[/tex]
This implies that;
[tex](g+h)(x)=x+2+4x^2[/tex]
Rewrite in standard form to obtain [tex](g+h)(x)=4x^2+x+2[/tex]
2) [tex](g-h)(x)=g(x)-h(x)[/tex]
This implies that;
[tex](g-h)(x)=x+2-4x^2[/tex]
Rewrite in standard form to obtain [tex](g+h)(x)=-4x^2+x+2[/tex]
3) [tex](g\bullet h)(x)=(x+2)(4x^2)[/tex]
We now substitute [tex]x=-3[/tex] to obtain;
[tex](g\bullet h)(-3)=(-3+2)(4(-3)^2)[/tex]
[tex](g\bullet h)(-3)=(-1)(36)[/tex]
[tex](g\bullet h)(-3)=-36[/tex]